The Association Between Hip-Shoulder Separation Angles and Technique Characteristics in World-Class High Jumpers - Nicholson, Gareth; Jongerius, Nils; Tucker, Catherine B.; Thomas, Aaron; Merlino, Stéphane; Bissas, Athanassios (Frontiers in Sports and Active Living, 2022)
Hip-shoulder separation (H-Ssep) has been widely researched in many sporting activities (e.g., golf) to provide information on the contribution of torso rotation to performance and injury. Although it is necessary for high jumpers to generate significant long-axis rotation to successfully clear the bar, limited information exists on H-Ssep for high jump athletes. As such, this study aimed to a) characterize the H-Ssep of world-class high jump athletes during competition, b) determine if differences exist between male and female athletes and c) to examine the relationship between H-Ssep and the biomechanical parameters used to describe high jump technique. Twenty-nine world-class high jumpers (17 males, 12 females) were recorded (120-200 Hz) during the 2017 and 2018 World Athletics Championship finals. H-Ssep was quantified at touchdown (TD) and take-off (TO) following manual digitizing (SIMI motion) and a number of other common biomechanical parameters were computed. The observed levels of H-Ssep at TD (−46 ± 12o) and TO (16 ± 11o) were in line with those reported previously for other sports. The magnitude of H-Ssep varied between individuals and showed significant associations with other approach and take-off characteristics. Significant differences in H-Ssep were not evident between male and female athletes despite significant differences in other performance- and technique-related parameters. These findings highlight the divergent take-off characteristics of world-class performers and their reliance on hip-shoulder interactions when generating long axis rotation. Coaches should be mindful of the mechanical and physical consequences of H-Ssep when developing technical models, conditioning interventions and coaching strategies.